The Effect of Peer Teaching Education on Diabetes Self-Care in Patients with Gestational Diabetes: A Quasi-Experimental Study - Oktavia, Lina; Astriana, Willy; Akbar, M Agung (Media Publikasi Cendekia Indonesia, 2025)
Gestational diabetes mellitus (GDM) is a global health concern requiring effective self-care, yet barriers such as limited social support and education persist. Peer teaching has emerged as a potential strategy to enhance self-care in GDM patients, though evidence of its effectiveness remains scarce. This quasi-experimental study aimed to evaluate the impact of peer teaching on diabetes self-care behaviors among GDM patients. The study involved 80 pregnant women with GDM, divided into an intervention group (receiving peer teaching) and a control group (receiving standard care). The intervention consisted of weekly 90-minute peer-led sessions over four weeks, focusing on practical self-care strategies. Self-care behaviors were assessed using the Diabetes Self-Management Instrument (DSMI) at baseline and post-intervention. Results revealed significant improvements in all DSMI subscales (self-integration, self-regulation, interaction with healthcare providers, self-monitoring, and adherence to therapy) in the intervention group (p < 0.001), with no comparable changes observed in the control group. The findings demonstrate that peer teaching effectively enhances self-care practices in GDM patients, particularly in glucose monitoring and treatment adherence. These results support integrating peer-led education into routine antenatal care for GDM, especially in resource-limited settings. Future research should explore long-term outcomes and scalability to strengthen implementation strategies